2010
DOI: 10.3892/ijo_00000793
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α-taxilin in hepatocellular carcinoma correlates with growth activity and malignant potential of the tumor

Abstract: Abstract. The membrane traffic system has been recognized to be involved in carcinogenesis and tumor progression in several types of tumors. ·-taxilin is a newly identified membrane traffic-related molecule, and its up-regulation has been reported in embryonic and malignant tissues of neural origin. In the present study, we analyzed the expression of ·-taxilin in relation to clinicopathological features of hepatocellular carcinomas (HCC) and proliferative activity of the tumor determined by proliferating cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…33,34 Alpha-taxilin (TXLNA) has been reported in renal cell cancer, hepatocellular cancer, and pancreatic cancer. [35][36][37] To our knowledge, no study has found an association between TXLNA and breast cancer. Nectin-4 (PVRL4) is expressed in cancer tissues such as breast cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…33,34 Alpha-taxilin (TXLNA) has been reported in renal cell cancer, hepatocellular cancer, and pancreatic cancer. [35][36][37] To our knowledge, no study has found an association between TXLNA and breast cancer. Nectin-4 (PVRL4) is expressed in cancer tissues such as breast cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have found that CEA levels were affected by drugs such as trastuzumab and paclitaxel 33,34 . Alpha‐taxilin (TXLNA) has been reported in renal cell cancer, hepatocellular cancer, and pancreatic cancer 35–37 . To our knowledge, no study has found an association between TXLNA and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TXLNA, for example, is a cancer suppressor gene in pancreatic cancer, yet it is a promoter of tumors in hepatocellular carcinoma and renal cell carcinoma, thus inducing their emergence and development. It was proposed by Natsuko Ohtomo et al that the TXLNA expression is linked to the augmented proliferation and poorly differentiated histological evaluation of hepatocellular carcinoma [ 7 ]. Tomoko Mashidori 1 et al found that the metastatic and invasive capacity of renal cell carcinoma was revealed to be augmented by a high expression of TXLNA [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, vesicular transport is involved in multiple processes of eukaryotic cell proliferation, and its function also suggests that this gene may be involved in tumor expression [ 6 ]. More than that, a few Studies have established TXLNA’s existence and manifestation in hepatocellular carcinoma, renal cell carcinoma, and pancreatic tumor cells [ 7 , 8 ]. In addition, Sueli M et al conducted real-time fluorescence quantitative PCR analysis of TXLNA genes using different grade astrocytic tumor samples in an experiment, confirming that their expression was higher compared to non-tumor CNS tissues [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taxilin is involved in Ca 2+ -dependent exocytosis in neuroendocrine cells 63 . Its expression is correlated with growth activity and malignant potential of hepatocellular carcinoma 64 . It was previously shown that inhibiting lysosomal exocytosis reversed invasiveness and chemoresistance in aggressive sarcoma cells 65 , which highlights the possible role of taxilin as a key-player in MT3-mediated CDDP trafficking and resistance in Nbl cells.…”
Section: Discussionmentioning
confidence: 99%